A novel fluorescent sensor based on imidazo[1, 2-a]pyridine for Zn2+. Issue 32 (14th March 2016) - Xiao, Shihua; Liu, Zheng; Zhao, Jinyan; Pei, Meishan; Zhang, Guangyou; He, Wei
Abstract : A novel chemosensorL1 for the detection of Zn 2+ based on imidazo[1, 2- a ]pyridine in C2 H5 OH–H2 O (9 : 1, v/v) buffer solution was designed and synthesized. Abstract : A novel chemosensorL1 for the detection of Zn 2+ based on an imidazo[1, 2- a ]pyridine in C2 H5 OH–H2 O (9 : 1, v/v) buffer solution was designed and synthesized.L1 showed a significant fluorescence enhancement in the presence of Zn 2+ over other competitive metal ions with a limit of detection of 6.8 × 10 −8 M. Upon the addition of Zn 2+, the resulting complexL1 -Zn 2+ could induce bathochromic shifts both in absorption and emission bands due to the intramolecular charge transfer process (ICT). The reason for fluorescence enhancement and color changes ofL1 towards Zn 2+ was demonstrated by density functional theory (DFT) and time-dependent density functional theory (TDDFT) calculations with 6-31G(d) basis sets using a suite of Gaussian 03 programs.